A prospective cohort study of severe sepsis-induced dyslipidemia and changes in D-dimer levels in children: do they affect the prognosis? - Tarek A. Abdelaziz; Mohamed Ali Abdou Mohamed; Weaam Ibrahim Ismail; Ibrahim Ali Ibrahim Idreis; Eman Gamal Baz (SpringerOpen, 2023)
Abstract Background The dyslipidemia and changes in D-dimer values that occur in children with severe sepsis remain unidentified. Objective The current research aimed to explore the relationship between D-dimer and lipid profile values, including total cholesterol (TC), lipoproteins, apolipoprotein A-V (Apo A-5), triglycerides (TG), and in-hospital nonsurvival in children with severe sepsis or septic shock in pediatric intensive care. Study design The study design is as follows: prospective cohort study. Participants Children with severe sepsis or septic shock who were admitted to the intensive care unit of a university pediatric hospital. Intervention Vital signs, sepsis assessment, pediatric sequential organ failure assessment (PSOFA) score, high-density lipoprotein (HDL), Apo A-5, TG, low-density lipoprotein (LDL), TC, D-dimer, mortality outcome, and pediatric risk of mortality (PRISM) III score were evaluated. Outcomes The primary outcome was in-hospital nonsurvival. Results The nonsurvivors had significantly higher D-dimer levels than the survivors, with a significant cutoff level of 0.87 μg/mL (AUC: 0.85, sensitivity: 93.3%, PVN: 90.6%, accuracy: 79.0%, PVP: 72.5%, and specificity: 64.7%). D-dimer was inversely correlated with WBC count and positively correlated with patient age, PRISM III score, PSOFA score, and INR. However, nonsurvivors had higher TG levels and lower TC, HDL, LDL, and Apo A-5 levels than survivors, but this variation was insignificant. Apo A-5 levels were inversely correlated with HDL and positively correlated with TG levels. Conclusions This study suggests that D-dimer is a promising biomarker for severe sepsis in children, with a mortality cutoff level of 0.87 μg/mL. However, lipid profiles are not predictors of sepsis-related mortality.